2009
DOI: 10.1128/jcm.02167-08
|View full text |Cite
|
Sign up to set email alerts
|

High Diversity ofMycobacterium tuberculosisGenotypes in South Africa and Preponderance of Mixed Infections among ST53 Isolates

Abstract: The reemergence of tuberculosis (TB) has become a major health problem worldwide, especially in Asia and Africa. Failure to combat this disease due to nonadherence or inappropriate drug regimens has selected for the emergence of multiple-drug-resistant (MDR) TB. The development of new molecular genotyping techniques has revealed the presence of mixed Mycobacterium tuberculosis infections, which may accelerate the emergence of drug-resistant strains. There are some studies describing the local distribution of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
64
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 38 publications
8
64
1
2
Order By: Relevance
“…All of these strains were isolated from retreatment patients and could therefore be explained by a mixed infection with sensitive and resistant strains. Mixed infections are seen in areas with high rates of TB and MDRTB (11,41). However, double alleles were identified by VNTR typing in one of three mixed strains only.…”
Section: Discussionmentioning
confidence: 99%
“…All of these strains were isolated from retreatment patients and could therefore be explained by a mixed infection with sensitive and resistant strains. Mixed infections are seen in areas with high rates of TB and MDRTB (11,41). However, double alleles were identified by VNTR typing in one of three mixed strains only.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that, had we the means to investigate all samples in this study by also using MIRU-VNTR typing, we may have identified more mixed infections. Of the 3 most commonly used techniques for genotyping M. tuberculosis isolates (IS6110-RFLP, spoligotyping, and MIRU-VNTR typing), it is MIRU-VNTR typing that has the greatest capacity to detect the presence of multiple strains, as has been previously demonstrated (11,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…This belief was first challenged when phage typing identified the presence of more than one M. tuberculosis strain in isolates obtained from a single patient (2,17). With the development of DNA fingerprinting (28) and other PCR-based genotyping methods (15,27) to differentiate M. tuberculosis strains, the presence of multiple strains within a single patient has been demonstrated during routine genotyping studies (5,19,20,24,33). The results from these and further studies designed to specifically examine mixed infections (1,10,20,22,23,29,32) have shown that they occur in different geographical settings among both HIV-negative and HIV-positive tuberculosis (TB) patients.…”
mentioning
confidence: 99%
“…However, some of these studies examine anecdotal cases (2) and others analyze this phenomenon only in specific M. tuberculosis lineages (35) or specific phenotypes (34). Those which follow population-based designs to determine the proportion of clonally complex TB cases are performed mainly in epidemiological contexts with a markedly high incidence of TB (8,10,29,30,35) and/or where the possibility of overexposure is more likely (28).…”
Section: Discussionmentioning
confidence: 99%
“…Several clonally complex phenomena have been observed, including mixed infections with more than one strain (29,30,35), simultaneous presence of clonal variants (microevolution phenomena) (1, 2), or even different distributions of strains/clonal variants infecting independent anatomical sites in the same patient (6,15).…”
mentioning
confidence: 99%